Chromatographic comparison of bupivacaine imprinted polymers prepared in crushed monolith, microsphere, silica-based composite and capillary monolith formats - Oxelbark, Joakim; Legido-Quigley, Cristina; Aureliano, Carla S.A.; Titirici, Maria-Magdalena; Schillinger, Eric; Sellergren, Börje; Courtois, Julien; Irgum, Knut; Dambies, Laurent; Cormack, Peter A.G.; Sherrington, David C.; De Lorenzi, Ersilia (Journal of Chromatography A, 2007)
A comprehensive comparison of five chromatographic stationary phases based on molecularly imprinted polymers is presented. Efficiency, imprinting factors, water compatibility and batch-to-batch reproducibility are discussed for crushed monolith, microspheres, two silica-based composites and capillary monoliths, all imprinted with the local anaesthetic bupivacaine. Synthesis protocol and chromatographic test conditions have been kept fixed within certain limits, in order to provide further insight into the strengths and weaknesses of the different formats. Excluding microparticles, all formats give satisfactory performance, especially in aqueous mobile phases. An assessment of batch-to-batch reproducibility in different mobile phases adds further value to this comparison study.